2007
DOI: 10.1364/oe.15.013574
|View full text |Cite
|
Sign up to set email alerts
|

Spatially varying regularization based on spectrally resolved fluorescence emission in fluorescence molecular tomography

Abstract: Abstract:Fluorescence molecular tomography suffers from being mathematically ill-conditioned resulting in non-unique solutions to the reconstruction problem. In an attempt to reduce the number of possible solutions in the underdetermined system of equations in the reconstruction, we present a method to retrieve a spatially varying regularization map outlining the feasible inclusion position. This approach can be made very simple by including a few multispectral recordings from only one source position. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The quantum yield was scaled to the wavelength range between 695 and 705 nm according to Eq. (16) in [16]. In the larger tank the fluorophore was mixed with the bulk solution in a concentration retrieving a fluorophore absorption coefficient of af = 3.9ϫ 10 −3 mm −1 .…”
Section: ͑4͒mentioning
confidence: 99%
“…The quantum yield was scaled to the wavelength range between 695 and 705 nm according to Eq. (16) in [16]. In the larger tank the fluorophore was mixed with the bulk solution in a concentration retrieving a fluorophore absorption coefficient of af = 3.9ϫ 10 −3 mm −1 .…”
Section: ͑4͒mentioning
confidence: 99%
“…Recent studies have also reported that plasma visfatin level was significantly increased from 29 ng/ml in normal controls to 41 ng/ml in a large population of patients with CKD [29]. In contrast to adiponectin, the higher the plasma levels of visfatin, the more severe the CKD, and a higher plasma level of visfatin predicts a higher mortality rate in these patients of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the spectrally adaptive property discussed above, the spatially dependent property in different regions remains a critical problem. We use a simple spatial information extractor dj called difference curvature [24][25][26] to distinguish edges from ramps in the presence of noise,…”
Section: Spectral-spatial Adaptive Unidirectional Variation Modelmentioning
confidence: 99%